2018
DOI: 10.1093/mnras/sty2993
|View full text |Cite
|
Sign up to set email alerts
|

Deep ALMA search for CO gas in the HD 95086 debris disc

Abstract: One of the defining properties of debris discs compared to protoplanetary discs used to be their lack of gas, yet small amounts of gas have been found around an increasing number of debris discs in recent years. These debris discs found to have gas tend to be both young and bright. In this paper we conduct a deep search for CO gas in the system HD 95086 -a 17 Myr old, known planet host that also has a debris disc with a high fractional luminosity of 1.5×10 −3 . Using the Atacama Large Millimeter/submillimeter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In subsection 2.1, we demonstrated that even if it is a member of LCC, the latest data predict that the RV should then be closer to 16±4 km s −1 and in the more likely case that it is a member of Carina, the RV should be close to 17.1±0.6 km s −1 , in perfect agreement with the spectroscopic measurement of 17±2 km s −1 (Moór et al 2013b). From this we can conclude that the tentative detection of gas from Booth et al (2019) must, in fact, just be a spurious noise signal and no gas has yet been detected in the HD 95086 debris disc.…”
Section: Gas In the Hd 95086 Debris Discsupporting
confidence: 82%
See 1 more Smart Citation
“…In subsection 2.1, we demonstrated that even if it is a member of LCC, the latest data predict that the RV should then be closer to 16±4 km s −1 and in the more likely case that it is a member of Carina, the RV should be close to 17.1±0.6 km s −1 , in perfect agreement with the spectroscopic measurement of 17±2 km s −1 (Moór et al 2013b). From this we can conclude that the tentative detection of gas from Booth et al (2019) must, in fact, just be a spurious noise signal and no gas has yet been detected in the HD 95086 debris disc.…”
Section: Gas In the Hd 95086 Debris Discsupporting
confidence: 82%
“…So far, however, no publication has considered the possibility that it is a member of a different association. Due to questions about its RV, particularly in relation to the possible presence of CO gas in its debris disc (Booth et al 2019), we have reason to question its association membership.…”
Section: Hd 95086mentioning
confidence: 99%
“…Alternatively, observations at a different wavelength could be used to measure the disc and clump spectral index and see if they differ, which could suggest that the observed residual is background emission. The difference in spectral index was used as an evidence for the extra-galactic origin of a clump in HD 95086 ALMA observations (Su et al 2017;Booth et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The spectral index has also been used to discriminate between possible origins of sub-mm emission (Su et al 2017;Booth et al 2019), since this differs between optically thin dust from planetesimal collisions, mm ≈2−2.5, and extra-galactic emission, mm ≈3−4. In §3.1.2 we derived the spectral index for the full disc of mm =2.34±0.29, which is consistent with measurements of other debris discs Ricci et al (2015a).…”
Section: Clumpiness From Extra-galactic Emission?mentioning
confidence: 99%